Anode-Dependent Impedance Rise in Layered-Oxide Cathodes of Lithium-Ion Cells. Issue 9 (1st January 2018) - Rodrigues, Marco-Tulio F.; Kalaga, Kaushik; Trask, Stephen E.; Shkrob, Ilya A.; Abraham, Daniel P.
Abstract : Nickel-rich Ni-Co-Mn (NCM) or Ni-Co-Al (NCA) layered-oxide positive electrodes (cathodes) allow high-voltage operation of lithium-ion cells with increased energy density, but their long-term cycling causes gradual increase in their impedance that slows down lithiation and delithiation of the material. Here we report that pairing of these cathodes with lithium titanate (Li4 Ti5 O12, LTO) negative electrodes (anodes) accelerates this impedance rise when compared to pairing with graphite (Gr) electrodes, during potentiostatic holds (calendar-aging) at sufficiently high (> 4.2 V vs. Li/Li + ) layered-oxide potentials. Our results suggest that gases generated in the cell play an important role in this impedance rise. In the graphite cells, these gases are gradually depleted by reactions at the Gr electrode, but such reactions do not occur at the LTO electrode. The generation and buildup of gases degrades the electron conduction network within the cathode, and also leads to modifications at the oxide-electrolyte interfaces, causing the observed impedance rise. The calendar-aging also alters cell capacity, with losses observed in the Gr cells and gains observed in the LTO cells. Possible causes and consequences of these changes in the lithium-ion inventory of the cells are discussed.